Angiotensina II intra-renal modula a expressão da óxido nítrico sintase neuronal na hipertensão renovascular 2R1C - Pereira, Thiago de Melo Costa (2005)
In physiological conditions, nitric oxide (NO) exerts a modulatory influence on renal blood flow mainly due the neuronal nitric oxide synthase (nNOS) enzyme isoform. Although some studies have demonstrated that the renal nNOS mRNA expression is modified in arterial hypertension (HÁ), it has not yet been shown how nNOS protein expression is modulated by endogenous angiotensin II (Ang II), a vasoconstrictor and a NO function inhibitor. Through the western blotting technique have been evaluate the relative role of HA and Ang II on the nNOS protein expression in the kidneys of renovascular hypertensive rats two-kidneys one clip (2K1C). The specific aim was to investigate the role of AT1 receptors and oxidative stress in modulating nNOS expression and the NO bioavaiability by GMPc quantification for enzymeimmunoassay. Then, the animals were divided in 4 groups: 2K1C (n=9), 2K1C+subpressor dose of losartan (10 mg/Kg/day in drinking water; n=4), 2K1C+subpressor dose of tempol (0.2 mmol/Kg/day in drinking water; n=6), and Sham (n=16), presenting values of MAP 179 ± 5 mmHg, 140 ± 7 mmHg, 181 ± 10 mmHg and 99 ± 3 mmHg, respectively. The nNOS expression was increased in the contralateral and clipped kidneys of the animals 2R1C when compared to SHAM group (0,43±0,03 vs. 0,14 ± 0,02 u.d.o. e 0,27±0,03 vs. 0,16±0,03 u.d.o. respectively), normalized in both kidneys in 2R1C + losartan when compared to SHAM group (0,24 ± 0,01 vs 0,27 ± 0,01 u.d.o e 0,21 ± 0,03 vs.0,29 ± 0,02 u.d.o., respectively). In 2R1C + tempol group, the nNOS expression was decreased in the contralateral kidney (0,27 ± 0,06 vs. 0,19 ± 0,06 u.d.o., respectively) but still increased in the clipped kidney when compared to SHAM group (0,35 ± 0,08 vs. 0,17 ± 0,03 u.d.o., respectively). The present results demonstrate that: 1) In the 2K1C renovascular hypertension model, the AT1 receptors and oxidative stress seem to be primary stimuli for increasing nNOS expression but not the HA per se; 2) The increase in nNOS expression does not reflects directly on the more NO bioavaiability in both kidneys (contralaetral or clipped); 3) The increase in nNOS expression induces a compensatory mechanism in order to maintain the renal homeostasis in this model of hypertension.